2021
DOI: 10.3390/ijms22094418
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet Motility Increases Following Viral Immune Stimulation

Abstract: Lipid droplets (LDs) have traditionally been thought of as solely lipid storage compartments for cells; however, in the last decade, they have emerged as critical organelles in health and disease. LDs are highly dynamic within cells, and their movement is critical in organelle–organelle interactions. Their dynamics are known to change during cellular stress or nutrient deprivation; however, their movement during pathogen infections, especially at very early timepoints, is under-researched. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Lipid droplets play a fundamental role in the host–pathogen relationship, as evidenced by the rapid increase in lipid droplet numbers following infection with virus ( Samsa et al, 2009 ; Monson et al, 2021 ), bacteria ( D’Avila et al, 2006 ; Kumar et al, 2006 ), fungi ( Sorgi et al, 2009 ), and protozoa ( Vallochi et al, 2018 ; Melo et al, 2003 ; D’Avila et al, 2011 ; Rodríguez et al, 2017 ). The life cycle of many viruses is intimately tied to the host’s lipid metabolism ( Thomssen et al, 1992 ; Herker and Ott, 2012 ).…”
Section: Lipid Droplets In the Diseased Brainmentioning
confidence: 99%
“…Lipid droplets play a fundamental role in the host–pathogen relationship, as evidenced by the rapid increase in lipid droplet numbers following infection with virus ( Samsa et al, 2009 ; Monson et al, 2021 ), bacteria ( D’Avila et al, 2006 ; Kumar et al, 2006 ), fungi ( Sorgi et al, 2009 ), and protozoa ( Vallochi et al, 2018 ; Melo et al, 2003 ; D’Avila et al, 2011 ; Rodríguez et al, 2017 ). The life cycle of many viruses is intimately tied to the host’s lipid metabolism ( Thomssen et al, 1992 ; Herker and Ott, 2012 ).…”
Section: Lipid Droplets In the Diseased Brainmentioning
confidence: 99%
“…In the model of infected astrocytes, cells were infected with ZIKV or stimulated with poly I:C, a dsRNA virus mimic. The LD displacement and average velocity in cells were significantly enhanced 2 h after infection or stimulation, indicating that the dynamics of LDs had changed in the early stage of pathogen infection, further supporting the emerging role of LDs in the innate host response [ 143 ]. Another study showed that hydroxysteroid (17β) dehydrogenase (HSD17B)12 promotes the replication of ZIKV and the production of infectious particles by increasing LD biosynthesis, which plays a key role in virus assembly.…”
Section: Roles Of Lds In the Zikv Life Cyclementioning
confidence: 95%
“…Like DENV, Zika virus (ZIKV) infection alters LD number as well as its mobility. 121 Qin et al showed that ZIKV infection also induces lipophagy by activating AMPK-ULK1 signaling in human hepatoma cells. 122 In placental cells, ZIKV modulates LDs in both infected and bystander cells and LD formation is required for ZIKV replication.…”
Section: Other Flaviviruses and Ldsmentioning
confidence: 99%
“…Like DENV, Zika virus (ZIKV) infection alters LD number as well as its mobility 121 . Qin et al showed that ZIKV infection also induces lipophagy by activating AMPK‐ULK1 signaling in human hepatoma cells 122 .…”
Section: Flaviviruses and Ldsmentioning
confidence: 99%